THE EFFECTIVENESS OF NETILMICIN SULPHATE INSTILATION ON THE URETHRA CATHETER REMOVAL PROCEDURE IN REDUCING THE INCIDENCE OF CATHETER ASSOCIATED URINARY TRACT INFECTION - Darma-Kusuma, I.G.; Duarsa, G.W.K.; Golden, N. (BALI MEDICAL JOURNAL, 2012)
Objective: Catheter associated urinary tract infection (CAUTI) is the most common complication of short-term indwelling catheters. The risk of this complication is increase along with the length of catheter insertion. There is no complete agreement of intravenous administration of prophylaxis antibiotic in reducing the incidence of CAUTI. Currently, antibiotic instilation into bladder was developed, however it is still a controversial issue. Therefore in this study we would like to see the effectiveness of this procedure in reducing the risk of CAUTI. Method: Single blind randomized controle trial was conducted on 40 eligible male patients treated at surgical ward, Sanglah Hospital between March and August 2012. Twenty patients had netilmicin sulfate instilation and anathor 20 patients treated without instilation procedure. Urine culture was taken before and after catheter removal. The number of colonies were analyzed according to the WHO criteria. In this study WHO critirion 3 was used with a significant bacteriuria of more 10 5 CFU / mL. Data were analyzed with Chi-square table and processed statistically with SPSS. Significance was set at p value <0.05 with 95% CI. Results: The mean age was 50.07 (SD 15.49) years. The avarage length of urinary catheterization was 5 days (range from 4 to 14 days). CAUTI was observed in 18 patients (45%); symptomatic was 11 patients (61.1%) and asymptomatic was 7 patients (38.9%). Statistic analysis showed that netilmicin sulfate insilation significantly reduced the risk of CAUTI (OR 0.028 ; CI 0.004 - 0.172). Conclusion: Netilmicin sulfate instilation prior to catheter removal significantly reduced the risk of CAUTI after short-term indwelling catheter.